EUCAST rapid antimicrobial susceptibility testing (RAST): analytical performance and impact on patient management. (15th February 2021) - Berinson, Benjamin; Olearo, Flaminia; Both, Anna; Brossmann, Nicole; Christner, Martin; Aepfelbacher, Martin; Rohde, Holger
Abstract: Background: The emergence of antibiotic-resistant species calls for fast and reliable phenotypic susceptibility testing to adapt clinical management as fast as possible. Objectives: We assessed the real-life performance of EUCAST rapid antimicrobial susceptibility testing (RAST) and analysed its impact on patient management. Methods: RAST was performed on clinical blood cultures containing Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa or Acinetobacter baumannii complex. Categorical agreement with VITEK2 was analysed. A pre-post quasi-experimental observational study was designed to compare antibiotic treatment in sepsis patients in the RAST patient group ( n = 51) and a historical control cohort ( n = 54). Results: In total, 436 isolates, corresponding to 2314 disc diameters, were measured; 18.4% of these measurements were in the area of technical uncertainty. For the 81.6% categorical results, which could be compared, 94.7% were in agreement, whereas 5.3% of the results were not. In the RAST group, optimal therapy was initiated on the same day as blood culture positivity, while this was the case in the historical group after 24 h. In six cases, RAST allowed for rapid antibiotic escalation. The 30 day mortality rate was lower in the RAST group, although this was not statistically significant. Conclusions: RAST provides a reliable tool to improve clinical management of sepsis patients by providing rapid phenotypic susceptibility data. While not necessarily being an instrument for de-escalation, especially in areas of low prevalence, early detection allows for timely coverage of resistant isolates. Thus, RAST significantly adds to successful antibiotic stewardship programmes.